Comparison of prevalences of cardiovascular risk factors between “normal” and “high” hemoglobin A1c groups in a population - Toshima, Hironori; Adachi, Hisashi; Turuta, Makoto; Hashimoto, Ryuichi; Tashiro, Hiromi (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1993)
Glycosylated hemoglobin A1c (HbA1c) was measured as a marker for impaired glucose metabolism in a population survey performed in a farming community, Tanushimaru. Subjects were 1084 males and 1083 females aged over 40 who participated in this population survey in 1989. Subjects were divided into two groups according to HbA1c level (HbA1c≤6.0 versus HbA1c>6.0). The prevalence of cardiovascular risk factors in each HbA1c group was analyzed by age and sex. The results were as follows ; 1) In both men and women, obesity (BMI≥26) was significantly more frequent in the “high” HbA1c group (HbA1c>6.0). 2) In men, frequency of hypertension (systolic blood pressure over 160mmHg and/or diastolic blood pressure over 95mmHg) were significantly higher in the “high” HbA1c group. 3) In women, hypercholesterolemia (T. cho≥220mg/dl) were significantly more frequent in the “high” HbA1c group. Clinically, it has been well known that impaired glucose metabolism is closely associated with cardiovascular risk factors. From the analysis of this field survey data, it was concluded that a high prevalence of various cardiovascular risk factors was present in the “high” HbA1c group. Hypertension in men and hypercholesterolemia in women, in particular, showed high relative risks even after adjustment for age.